Analisis Explotasi Keamanan Web Denial of Service Attack - Siregar, Junita Juwita (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Internet network which is public and global is unsafe, so the security of public Internet-based information system needs to be considered. When a data is sent from one computer to another on the Internet, it will pass through a number of other computers that are meant to give the user an opportunity to take over one or several computers. denial of service attacks is one of the web security systems which can inhibit the activity of the work of a service even turn it off, so the authorized user cannot use the service. There is an attempt of certain parties to prevent a user access to a system or network by flooding the traffic network with so much data from unregistered users. It makes the user unable to log into the network system. The purpose of this paper is to analyze the cause of the denial of service attack on a web system using literature study. The result of this research is a method to overcome denial of service attack as well as the prevention techniques. This study concludes that securing techniques should be implemented extra carefully on DoS attacks (Denial-of-Service Attacks). Therefore, the attacker cannot overwhelm the network IP address and disrupt communication between a server and its client that may reject user’s request access to a system or a network service provided by a host.